ECM remodeling in hypothyroidism-associated MAFLD: mechanisms, clinical relevance, and therapeutic targets - Wang, Tianzhen; Duan, Liyun; Zhao, Beiying; Zhang, Jingbin; Yu, Yongjiang; Zhao, Jinyue (Frontiers in Immunology, 2025)
Metabolic dysfunction–associated fatty liver disease (MAFLD) is a major chronic liver disease increasingly linked to endocrine and immunometabolic dysregulation. Hypothyroidism, both overt and subclinical, has emerged as a significant endocrine risk factor for MAFLD. Extracellular matrix (ECM) remodeling, a hallmark of fibrosis, represents a crucial but underexplored mediator in this process. This review highlights how altered thyroid hormone (TH) and thyroid-stimulating hormone (TSH) signaling promote ECM remodeling through metabolic, inflammatory, and fibrogenic pathways, with emphasis on hepatic stellate cell (HSC) activation and immune reshaping. We further summarize ECM-derived biomarkers and emerging therapeutic strategies, including THRβ agonists and ECM-targeted approaches.